Enhancing superconducting properties of YBa2Cu3O7- ẟ through Nd2O3 addition prepared using modified thermal decomposition method - Mohamed, Arebat Ryad Alhadei; Awang Kechik, Mohd Mustafa; Kien, Chen Soo; Pah, Lim Kean; Baqiah, Hussien; Mohd Shariff, Khairul Khaizi; Hong, Yap Siew; Peh, Hoo Keong; Shaari, Abdul Halim; Humaidi, Syahrul; Miryala, Muralidhar (Springer, 2024)
Polycrystalline YBa2Cu3O7−δ (Y-123) samples with different varying weight percentages (x = 0.0, 0.1, 0.3, 0.5, 1.0, and 5.0 wt.%) of neodymium oxide (Nd2O3) addition have been successfully synthesized using a modified thermal decomposition method (DM) under ambient conditions. X-ray diffraction (XRD) analysis revealed favorable orthorhombicity values (~ 0.008) for the Y-123 crystal structure, and an estimated oxygen content close to the theoretical value (~ 6.8), along with the presence of light secondary phases such as Y2BaCuO5 (Y-211) and BaCuO2. For FESEM analysis, it was found that 5.0 wt.% Nd2O3 increased porosity and reduced grain size, negatively impacting superconductivity. Conversely, 0.5 wt.% Nd2O3 promoted significant grain growth, leading to enhanced grain contact and a denser microstructure. Electrical resistivity measurements confirmed superconducting transitions in all samples. Notably, the 0.5 wt.% Nd2O3 sample exhibited an optimal Tc-onset of 94.14 K with a narrow transition width ΔTc of 4.04 K. In contrast, the higher 5.0 wt.% Nd2O3 concentration resulted in a broader ΔTc of 7.47 K, suggesting the lower doping provided more optimal superconducting performance. AC susceptibility measurements corroborated these findings. This DM method offers a cost-effective approach for Y-123 synthesis, with potential for further optimization through alkali metal doping to reduce costs and environmental impact.